Growth of T-Strain Mycoplasmas in Medium Without Added Urea: Effect of Trace Amounts of Urea and of a Urease Inhibitor - Masover, G. K. (1974)
Urea is currently considered to be a requirement for the propagation of T-strain mycoplasmas. We report here the replication of T-strain 960 (ATCC 25023) in media prepared from dialyzed components with added putrescine and allantoin but without added urea, or in dialyzed medium containing small amounts of added urea. The least amount of urea which allowed growth in the medium without allantoin was above 10 μg/ml. The amount of urea estimated to contaminate the added allantoin or putrescine was 5 μg/ml or less, which is insufficient to support T-strain replication. T-strain 960 was grown in the presence of urea and the urease inhibitor acetohydroxamic acid AHA where the organisms multiplied at a slower rate in the presence of AHA than in its absence. Urea hydrolysis occurred with concomitant ammonia accumulation and pH increase in cultures with AHA added.